2007
DOI: 10.1080/10476210701533118
|View full text |Cite
|
Sign up to set email alerts
|

“Yeah, but I still don't want to deal with it”. Changes in a Teacher Candidate's Conceptions of Inclusion

Abstract: This study documents one teacher candidate's conceptions about the inclusion of children with special needs in the general education classroom and how these conceptions changed over time.The study illustrates which experiences contributed to an individual's evolving understandings and changing attitudes towards inclusion. Throughout a 15-week literacy methods course, the researcher collected data in the form of observations, interviews, course reflections, and other written assignments. Using grounded theory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…They note that the values that teacher trainees hold form the foundation for developing knowledge necessary for working in inclusive classrooms. This assertion aligns with Boling (2007) view that teacher educators should influence trainees to challenge prior assumptions and beliefs as a requisite for them to implement inclusion. John and Fuller 2013, however, indicate that even when training is provided, some trainees still leave initial teacher education without the knowledge needed to work with future children with special needs.…”
Section: 1problem Statementsupporting
confidence: 64%
See 1 more Smart Citation
“…They note that the values that teacher trainees hold form the foundation for developing knowledge necessary for working in inclusive classrooms. This assertion aligns with Boling (2007) view that teacher educators should influence trainees to challenge prior assumptions and beliefs as a requisite for them to implement inclusion. John and Fuller 2013, however, indicate that even when training is provided, some trainees still leave initial teacher education without the knowledge needed to work with future children with special needs.…”
Section: 1problem Statementsupporting
confidence: 64%
“…The colleges had teacher educators who are trained in special needs education. The trainers have a key role to influence trainees to appreciate their future professional responsibility of ensuring the provision of education for all (Boling 2007;Wormnaes 2008). The data, however, shows that some of the teacher trainers did not have training in the area of hearing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent in the literature is the claim that such discourses strengthen divisive constructions of education. (Boling, 2007;Florian, 2010;Forlin, 2010;Rouse, 2010;Slee, 2010). Thomas and Glenny (2005) locate their origins in the rationalist epistemologies which have perpetuated a preoccupation with correctives, special techniques and cures, asserting that this has led teachers to believe that they do not have the knowledge and skill to teach all children.…”
Section: The Discourses Of 'Expertism'mentioning
confidence: 99%
“…The results indicated that the program had a positive effect on preservice teachers' attitudes for teaching in inclusive settings and that the positive attitudes significantly increased after the field experience component. A study conducted by Boling (2007) provided an in-depth description of one preservice teacher's change in attitude towards inclusion as she participated in an inclusion course combined with field experiences. At the onset of the study, the participant expressed feelings of confusion, concern, nervousness, and generally struggled with the idea of inclusion.…”
Section: Preservice Teacher Attitudesmentioning
confidence: 99%